A system of parallel program performance analysis for clusters - Zhumatiy, S.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2005)
The article describes a system for analyzing the effectiveness of parallel programs. The main purpose of the system is to facilitate the adaptation of parallel programs to modern cluster installations, to speed up the process of finding bottlenecks in a parallel program.